God (≡ Elohim), The First Small World Network - Ausloos, Marcel (Frontiers in Physics, 2022)
In this article, the approach of network mapping of words in literary texts is extended to “textual factors”: the network nodes are defined as “concepts”; the links are “community connexions.” Thereafter, the text network properties are investigated along modern statistical physics approaches of networks, thereby relating network topology and algebraic properties to literary text contents. As a practical illustration, the first chapter of Genesis in the Bible is mapped into a 10-node network, as in the Kabbalah approach, mentioning God (≡ Elohim). The characteristics of the network are studied starting from its adjacency matrix and the corresponding Laplacian matrix. Triplets of nodes are particularly examined in order to emphasize the “textual (community) connexions” of each agent “emanation,” through the so-called clustering coefficients and the overlap index, hence measuring the “semantic flow” between the different nodes. It is concluded that this graph is a small world network and weakly dis-assortative, because its average local clustering coefficient is significantly higher than a random graph constructed on the same vertex set.